Telemetry reveals rapid duel-driven canary song plasticity in a competitive social environment - Alcami, Pepe; Ma, Shouwen; Gahr, Manfred (Frontiers in Psychology, 2025)
Singing by songbirds is a sexually selected, complex motor skill that is learned during juvenile development. In open-ended learners, adult songs are plastic, that is, birds retain the ability to change their songs. In some seasonal open-ended learners, including canaries, songs become stable at the onset of each breeding season. However, whether context-dependent plasticity of songs occurs during the breeding season remains elusive. We used custom-made telemetric backpack sound recording technology in five groups of canaries to monitor song-based communication from three males in competition for females during the breeding season. This allowed us to record each male’s songs during social interactions. We show that canaries proactively overlap their songs in time during aggressive vocal exchanges that we call duels. Birds that engage in duels take leader or follower roles on a song-to-song basis. When a male canary leads a duel, his songs last longer relative to his solo songs, increasing the chance to outlast the follower’s song. Moreover, the durations of leader and follower songs in duels are correlated, suggesting an interactive online adjustment of their songs. Remarkably, in each group, only two out of the three males extensively engage in duels whereas the third canary rarely participates. Overall, our findings reveal context-dependent behavioral flexibility of male-directed canary song signaling, characterized by a moment-to-moment plasticity different from the slow, well-studied seasonal plasticity. By their context-dependent modulation of the relative timing and duration of vocal exchanges, canary duels offer a window into the social cognitive abilities of songbirds.